2017
DOI: 10.1016/j.ijrefrig.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental phase diagram of the dodecane–tridecane system as phase change material in cold storage

Abstract: Highlights: C12H26-C13H28 system has a congruent minimum-melting solid solution and polymorphs  The minimum-freezing 17.7 mol% C13H28 blend (at -16 to -12 °C ) is a potential PCM  17.7 mol% C13H28 blend freezes with an enthalpy of 165 kJ kg -1 and no supercooling  The system has a minimum-melting trend, but has no eutectic as literature proposed  Extensive physicochemical studies needed to explain melting/freezing discrepancies AbstractIntegrating thermal storage with phase change materials (PCMs) in refr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…This effect can be prevented if the initial composition of the PCM is adjusted to circumvent the region of incongruent melting [14,15]. Phase diagrams are in this case very useful [16]. Incongruent melting is observable already on material scale, since it is an intrinsic problem due to a unstable material composition.…”
Section: Corrosion Of Salt-hydrates In Combination With Different Matmentioning
confidence: 99%
“…This effect can be prevented if the initial composition of the PCM is adjusted to circumvent the region of incongruent melting [14,15]. Phase diagrams are in this case very useful [16]. Incongruent melting is observable already on material scale, since it is an intrinsic problem due to a unstable material composition.…”
Section: Corrosion Of Salt-hydrates In Combination With Different Matmentioning
confidence: 99%
“…Yilmaz et al 64 presented the liquidus line of C 12 -C 13 and found a maximum melting point of -3.3°C at 80% C 13 , whereas Ventolà et al 29 identified a eutectic composition in this system. Most recently, Gunasekara et al 40,[42][43] carried out an overall experimental investigation of C 12 -C 13 , The obtained phase diagram indicated a congruent minimum-melting solid solution and polymorphs phases at lower temperatures. However, the system does not represent a eutectic, which is against to phase diagrams proposed by the Yilmaz et al 64 and Ventolà et al 29 .…”
Section: Binary Systemsmentioning
confidence: 99%
“…However, some of the C n blends were still missing. Therefore, based on their work, Table summarized more comprehensive binary C n mixtures (C 8 –C 50 ) by listing the PCM-interesting characteristics, and the temperature range is from 211.7 to 359.1 K (−61.5 to 86.0 °C). ,− The compositions are either weight, molar, or volumetric percentage, while the enthalpies are either kJ/kg or kJ/mol.…”
Section: Pure N-alkanes and Their Blends As Pcmsmentioning
confidence: 99%
“…[6][7][8][9][10] Several materials are commonly used, among which the most used are expanded polystyrene (EPS), extruded polystyrene (XPS) and polyurethane foam. 11,12 Rigid polyurethane foam (PUF), together with EPS, is nowadays one of the most widely used thermal insulation material, 4,13,14 as it exhibits low thermal conductivity (λ between 0.022 and 0.040 W/mÁK), coupled with lightness (40-120 kg/cm 3 ) and cheapness (close to 3.40 €/kg). [15][16][17][18][19] In the refrigeration sector, PUF is typically sprayed between the inner and outer envelope of freezers free to expand, but it can also be produced as panels for other use like in buildings.…”
Section: Introductionmentioning
confidence: 99%